Factors Influencing Consumers' Intention To Use Self-service Technology In Saudi Arabia Retail Industry - M, Khalufi Nasser Ali (2022)
This study used the Technology Acceptance Model (TAM) and the Diffusion of Innovation Theory (DIT) as a theoretical background. It extends TAM and DIT theories to self-service technology and investigates the factors influencing consumers’ intention to use self-service technology in the Saudi Arabian retail industry. This research study is built up to investigate various factors. These factors are social influence, need for interaction, technology anxiety, hedonic value, perceived usefulness, perceived ease of use, compatibility, perceived trust, and perceived risk that are all prospective influencing variables on attitudes towards self-service technology usage and consumer’s intention to use self-service technology. In addition, this study also investigated the mediating effect of consumers’ attitudes toward using self-service technology in the retail sector, focusing on fast-food restaurants and cinema theatres in Saudi Arabia. A total of 462 Saudi customers responded to the survey in this study. It has been found that the influences of compatibility, perceived ease of use, perceived usefulness, hedonic value, and social influence are significant, positive, and directly affect attitudes towards self-service technology. A direct influence of each need for interaction, perceived risk, and technology anxiety was found on consumers’ attitudes towards the usage of self-service technology, each of which was negative and significant.